Interacting climate change factors (CO2 and temperature cycles) effects on growth, secondary metabolite gene expression and phenotypic ochratoxin A production by Aspergillus carbonarius strains on a grape-based matrix - Cervini, Carla; Verheecke-Vaessen, Carol; Ferrara, Massimo; García-Cela, Esther; Magistà, Donato; Medina, Angel; Gallo, Antonia; Magan, Naresh; Perrone, Giancarlo (Elsevier, 2019)
Little is known on the impact that climate change (CC) may have on Aspergillus carbonarius and Ochratoxin A (OTA) contamination of grapes, especially in the Mediterranean region where in CC scenarios temperature are expected to increase by +2–5 °C and CO2 from 400 to 800/1200 ppm. This study examined the effect of (i) current and increased temperature in the alternating 11.5 h dark/12.5 h light cycle (15–28 °C vs 18–34 °C), representative of the North Apulia area, South Italy and (ii) existing and predicted CO2 concentrations (400 vs 1000 ppm), on growth, expression of biosynthetic genes (AcOTApks, AcOTAnrps, AcOTAhal, AcOTAp450, AcOTAbZIP) and regulatory genes of Velvet complex (laeA/veA/velB, “velvet complex”) involved in OTA biosynthesis and OTA phenotypic production by three strains of A. carbonarius. The experiments made on a grape-based matrix showed that elevated CO2 resulted in a general stimulation of growth and OTA production. These results were also supported by the up-regulation of both structural and regulatory genes involved in the OTA biosynthesis. Our work has shown for the first time that elevated CO2 concentration in the Mediterranean region may result in an increased risk of OTA contamination in the wine production chain.
Keywords: black aspergilli; alternating temperatures; carbon dioxide; mycotoxins; ecophysiology; biosynthetic genes